Behavior of dissolved nutrients in the marine area opposite to a sewage drainage in Afamia at Lattakia coast - Krawi, Hazem; Darwich, Firuz; Laika, Hussam Eddin; Joulak, Samar (Latakia University Journal -Biological Sciences Series, 2019)
This study Focused on determination of the most important hydrochemical properties of the sewage drainage area of Afamia via determination of nutrient concentrations (nitrate, nitrite, ammonia, phosphates and silicates) and Chlorophyll a. Water samples were collected from several sites of the area opposite to sewage drainage of Afamia area between March 2017 and January 2018. The highest concentrations of nutrients throughout the year were reported at the closest point to the sewage drainage (A300). A decreasing in the concentrations combined with salinity gradient was observed by moving away from drainage point, which is the main source of nutrients that are distributed to the next sites. Concentrations of nutrients showed a clear gradient during rainy months while drought months were characterized by lesser gradations. The annual rate of ammonium of total inorganic nitrogen was higher at the nearest site to the drainage point. This ratio decreased by moving away from drainage point in contrast of nitrate. Statistical study revealed a direct significant relationship between the concentrations of DIN, PO4-3 and SiO3-2. يهتم هذا البحث بدراسة أهم الخصائص الهيدروكيميائية لمياه منطقة مصب الصرف الصحي في أفاميا عبر تحديد تركيز الشوارد المغذية (النترات والنتريت والأمونيوم والفوسفات والسيليكات) والكلوروفيل aفي عينات مائية جمعت من عدة مواقع من المنطقة البحرية المقابلة لمياه الصرف الصحي في أفاميا خلال الفترة الممتدة بين آذار 2017 وكانون الثاني 2018. رصدت أعلى التراكيز للشوارد المغذية في النقطة الأقرب للمصب A300 ثم تناقصت هذه التراكيز بالابتعاد عن فوهة المصب متوافقاً مع تدرج ملوحة المياه خلال جميع الطلعات البحرية، حيث شكّلت نقطة المصب المصدر الرئيس للمغذيات التي يتم توزيعها إلى باقي المحطات. أبدت تراكيز الشوارد المغذية تدرجاً واضحاً خلال الأشهر ذات الهطولات المطرية المرتفعة بينما امتازت أشهر الجفاف بتدرج أقل امتداداً. كان المعدل السنوي لنسبة شوارد الأمونيوم من الآزوت اللاعضوي الكلي أعلى في المحطة الأقرب لنقطة الصرف الصحي وتناقصت هذه النسبة بالابتعاد عن نقطة الصرف على عكس شوارد النترات. أظهرت الدراسة الإحصائية وجود علاقة ارتباط طردية قوية بين تراكيز كل من DIN وPO4-3 وSiO3-2.